Strategi Edukasi Berbasis Literasi dalam upaya meningkatkan Budaya Keselamatan Pasien di RSUD Kabupaten Bekasi - Subardi, Arda Yunita; Wijaya, Anna Maria Nurhayati; Yuliana, Roma (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Patient safety is one of the main pillars in improving the quality of health services. In the preliminary study, it was found that the implementation of patient safety was low, so it is necessary to increase knowledge and understanding related to patient safety. This study aims to evaluate the effectiveness of literacy-based education strategies in improving the understanding and implementation of patient safety. This study uses both descriptive analytical methods to explain the education strategy through the applied Learning Model and Method, as well as quasi-experimental methods with a pretest-posttest design involving hospital staff to assess the effectiveness of learning. The literacy-based education program is designed using an interactive approach, such as e-learning modules, simulation videos, and PDSA and FMEA competitions to trigger brainstorming and group discussions in all units as learning and sharing of patient safety experiences. This will improve critical and analytical thinking skills in solving patient safety problems in their work units. The focus of the education material covers 6 (six) patient safety targets. The results of this study showed a significant increase in medical personnel's understanding of patient safety by up to 78% and an increase in active participation of units in PDSA learning by up to 100%. In addition, there was a reduction in Adverse Events (KTD) by up to 30% after the implementation of the education program. This study concludes that literacy-based education strategies are an effective approach and can be integrated into routine training systems in health facilities to improve patient safety culture.